NOBF4-Mediated Assembly of the Sydnone Imine Scaffold in the Synthesis of Double Nitric Oxide Donors - Shuvaev, Alexander D.; Zhilin, Egor S.; Fershtat, Leonid L. (Synthesis, 2023)
A direct approach toward the construction of furoxan-sydnone imine double NO-donors involving the NOBF4-mediated nitrosation–cyclization sequence of α-amino nitriles as a key synthetic step was developed. The described protocol excludes the isolation of carcinogenic N-nitrosamines, operates broad substrate scope, and enables the preparation of fully substituted sydnone imines linked to the furoxan ring via different linkers or directly through C–C bond. Synthesized library of furoxan-sydnone imine hybrids demonstrated a promising ability to release NO in a wide range of concentrations which is useful for various biomedical insights.
Keywords: nitric oxide; cyclization; nitrogen heterocycles; mesoionic heterocycles; molecular hybridization